PEMBINAAN MASYARAKAT DALAM PEMANFAATAN TEKNOLOGI INFORMASI PELAKSANAAN JARINGAN SUMBER DAYA AIR SUMATERA II PROV. SUMATERA UTARA SUNGAI PANTAI II DI LINGKUNGAN PKL MASHYUR, KECAMATAN MEDAN JOHOR - Lasrida Sigalingging; Dinaria br. Sembiring; Nurul Husnah Harahap; Evi Syuriani; Maslan Sihombing; Masriani Mery Rosmida Silalahi (Universitas Methodist Indonesia, 2021)
Community Service aims to foster the society on the advantages of the information technology in the Implementation of Water Resources Network Sumatera II Province of North Sumatera Sungai Pantai II in the society of the people in Lingkungan PKL Mashyur, Kecamatan Medan Johor. The community service is to socialize and to empower the people of the area to get knowledge and skill in using the media of technology of information in public service of how to get the public service fast, right and simple. This nurturing is related to the condition of the information service to the society on how to build the information comes at the right time, the right place to the right target and right usage more in the situation of pandemic Covid 19 today. The use of computers in society is quite affected more by the attitude of the people as users. The community that will be trained are the people who live in the Environment of PKL Mashyur, Kecamatan Medan Johor, of the total of 25 people whose livelihoods area as farmers and farm laborers. The availability of adequate academics in giving lectures about the use of technology of information in the program of study Computerization of accounting of AMIK MEDICOM, the enthusiasm of the participants, the support of the Village Head and the Head of the Environment for the implementation of activities and funds supported by AMIK MEDICOM are the supporting factors of the implementation of this activities. The problem came when the time used to give the learning and coaching is too much limited. This training will give benefits to the participants, they are to enable the society to understand and to develop their skill in using the technology of information as a medium to get the right information at the right time, for the right use and target.